In Situ Endothelialization Promoted by SEMA4D and CXCL12 for Titanium-Based Biomaterials - Cui, Yuanyuan; Zhou, Feng; Wei, Lai; Song, Qiang; Tan, Jianying; Zeng, Zheng; Chen, Junying; Huang, Nan (Seminars in Thrombosis and Hemostasis, 2018)
In situ endothelialization, aiming to create implantation surfaces capable of self-endothelialization, seems to be an extremely promising solution, particularly on those blood-contacting surfaces. In this research study, we immobilized the soluble semaphorin 4D (SEMA4D) and C-X-C motif chemokine ligand 12 (CXCL12) biomolecules together with heparin onto the metal-based biomaterial surfaces to achieve in situ endothelialization of modified samples both by stimulating the neighboring endothelial cells (ECs) migration and by capturing the circulating endothelial progenitor cells (EPCs) directly from the blood circulation. X-ray photoelectron spectroscopy data demonstrate the successful immobilization of SEMA4D and CXCL12. Due to the presence of heparin, hemocompatibility was also improved after modification. Although EC migration was mainly mediated by SEMA4D with the coordination of CXCL12, EC proliferation and haptotaxis property were also enhanced, while EC chemotaxis was slightly suppressed because the further immobilization of CXCL12 influences the release of SEMA4D. The results of the ex vivo EPC capturing assay indicated the mobilization of CXCL12 promotes EPC adhesion. In vivo implantation further demonstrated that CXCL12 cooperates with SEMA4D to promote a process of in situ endothelialization.
Keywords: in situ endothelialization; endothelial cell migration; endothelial progenitor cell; SEMA4D; CXCL12